Analysis of the Gene Expression Profile of Stromal Pro-Tumor Factors in Cancer-Associated Fibroblasts from Luminal Breast Carcinomas - Noemi Eiro; Sandra Cid; María Fraile; Jorge Ruben Cabrera; Luis O. Gonzalez; Francisco J. Vizoso (Diagnostics, 2020)
Luminal tumors are the most frequent type of breast carcinomas showing less tumor aggressiveness, although heterogeneity exists in their clinical outcomes. Cancer-associated fibroblasts (CAFs) are a key component of the tumor stroma which contribute to tumor progression. We investigated by real-time PCR the gene expression of 19 factors implicated in tumor progression. Those factors included the calcium-binding protein S100A4, several growth factors (FGF2, FGF7, HGF, PDGFA, PDGFB, TGFβ, VEGFA, and IGF2), and we also studied inflammatory cytokines (IL6 and IL8), chemokines (CCL2, CXCL12), important proteases (uPA, MMP2, MMP9 and MMP11), the nuclear factor NFκB, and the metalloprotease inhibitor TIMP1, from luminal A and luminal B breast carcinoma CAFs. We performed a similar analysis after co-culturing CAFs with MCF-7 and MDA-MB-231 breast cancer cell lines. MMP-9 and CCL2 gene expressions were higher in CAFs from luminal B tumors. We also found different patterns in the induction of pro-tumoral factors from different CAFs populations co-cultured with different cancer cell lines. Globally, CAFs from luminal B tumors showed a higher expression of pro-tumor factors compared to CAFs from luminal A tumors when co-cultured with breast cancer cell lines. Moreover, we found that CAFs from metastatic tumors had higher IGF-2 gene expression, and we detected the same after co-culture with cell lines. Our results show the variability in the capacities of CAFs from luminal breast carcinomas, which may contribute to a better biological and clinical characterization of these cancer subtypes.